2019
DOI: 10.1259/bjro.20190022
|View full text |Cite
|
Sign up to set email alerts
|

Current status of stereotactic ablative body radiotherapy in the UK: six years of progress

Abstract: Objective: To update the 2012 UK stereotacticablative radiotherapy (SABR) Consortium survey and assess the development of SABR services across the UK over the past 6 years. Use the results to share practice and continue to drive forward technique development, aid standardization and by highlighting issues, improve access to SABR services and trials across the UK. Methods: In January 2018, an online questionnaire was sent by the UK SABR Consortium to 65 UK radiotherapy institutions covering current service prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…41,42,46 Measurements in lung phantoms, particularly of small fields, are becoming increasingly important as more departments attempt to commission or validate treatment planning system calculations for stereotactic ablative radiotherapy treatments of small lung lesions. 21,26,27 Film measurements in lung phantoms should be corrected using values in Tables I--III, as shown in Eq. (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42,46 Measurements in lung phantoms, particularly of small fields, are becoming increasingly important as more departments attempt to commission or validate treatment planning system calculations for stereotactic ablative radiotherapy treatments of small lung lesions. 21,26,27 Film measurements in lung phantoms should be corrected using values in Tables I--III, as shown in Eq. (1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, between 2012 and 2018 the number of radiotherapy departments in the UK utilizing lung SBRT increased from 31% to 76 % (with the remaining 24% planning to implement SBRT within 2 yr). 21 In another recent example, 84% of radiotherapy departments in New South Wales, Australia are treating patients with lung SBRT. 22 Lung tumor sizes being treated can be as small as 3 mm in diameter, 23 and advancing imaging techniques and motion management strategies are allowing margins to be reduced, sparing more healthy lung tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional radiotherapy is associated with inferior outcomes compared with SBRT for peripheral lesions, and limited access to SBRT across the United Kingdom was likely a contributing factor with only approximately 40% of centers offering lung SBRT in 2018. 10 For stage III NSCLC, 60% of patients received only either active palliative treatment or best supportive care. Of the approximate 30% receiving radical-intent treatment, only 18% received multimodality treatment, with sequential chemoradiotherapy being offered approximately twice as often as concurrent.…”
Section: Radiotherapymentioning
confidence: 99%
“…The paper by Phillips et al [2] reports that the percentage of patients undergoing SABR in England has increased from 64% in 2015 to 73% in 2016. Importantly, the 2018 updated UK SABR Consortium Audit [9] documents an increase in SABR provision, with the number of centres commissioned to deliver SABR rising from 12 in 2012 to 38. However, the 2018 survey also showed that SABR is not currently offered in around 40% of UK radiotherapy centres, a finding that highlights that the concerns raised by Phillips et al [2] from the 2015e2016 data are still present.…”
mentioning
confidence: 99%